Could breaks reduce general practitioner burnout and improve safety? A daily diary study - Hall, Louise H.; Johnson, Judith; Watt, Ian; O’Connor, Daryl B. (PloS one, 2024)
Rates of burnout are currently at record high levels, and GPs experience higher burnout than many other specialties. Organisational interventions may reduce burnout, but few studies have investigated these in primary care. The current study investigated whether breaks, both with and without social interactions, were associated with burnout and patient safety perceptions in GPs. A within-subjects, interval contingent, quantitative daily diary design. UK GP practices. Participants completed questionnaires at baseline measuring demographic variables, burnout and patient safety perceptions. They then completed a questionnaire in the evening each day for a week which captured whether they had taken a break that day, whether it involved a positive social interaction, burnout (comprising subscales of disengagement and exhaustion), positive and negative affect and patient safety perceptions. The data were analysed using hierarchical linear modelling to assess same-day and next-day associations. We included 241 responses from 58 GPs for analysis. Taking at least one break (involving any or no social interactions) was associated with lower disengagement that day and lower exhaustion the next day. Taking at least one break involving a positive interaction was associated with 1) lower disengagement, exhaustion, overall burnout and negative affect on the same day, as well as higher positive affect and improved perceptions of patient safety, and 2) lower exhaustion and improved patient safety perceptions on the next day. Organizing daily team or practice breaks where staff can socialise may help to reduce burnout and improve perceptions of patient safety.